Telemonitoring of Crohn's Disease and Ulcerative Colitis (TECCU): Cost-Effectiveness Analysis - Del Hoyo, Javier; Nos, Pilar; Bastida, Guillermo; Faubel, Raquel; Muñoz, Diana; Garrido-Marín, Alejandro; Valero-Pérez, Elena; Bejar-Serrano, Sergio; Aguas, Mariam (JMIR Publications, 2019)
BackgroundAlthough electronic health interventions are considered safe and efficient, evidence regarding the cost-effectiveness of telemonitoring in inflammatory bowel disease is lacking. ObjectiveWe aimed to evaluate the cost-effectiveness and cost-utility of the Telemonitorización de la Enfermedad de Crohn y Colitis Ulcerosa (Telemonitoring of Crohn's Disease and Ulcerative Colitis [TECCU]) Web platform (G_TECCU intervention group) for telemonitoring complex inflammatory bowel disease, compared with standard care (G_control) and nurse-assisted telephone care (G_NT intervention group). MethodsWe analyzed cost-effectiveness from a societal perspective by comparing the 3 follow-up methods used in a previous 24-week randomized controlled trial, conducted at a tertiary university hospital in Spain. Patients with inflammatory bowel disease who initiated immunosuppressants or biologic agents, or both, to control inflammatory activity were recruited consecutively. Data on the effects on disease activity (using clinical indexes) and quality-adjusted life-years (using the EuroQol 5 dimensions questionnaire) were collected. We calculated the costs of health care, equipment, and patients' productivity and social activity impairment. We compared the mean costs per patient, utilities, and bootstrapped differences. ResultsWe included 63 patients (21 patients per group). TECCU saved €1005 (US $1100) per additional patient in remission compared with G_control (95% CI €-13,518 to 3137; US $-14,798 to 3434), with a 79.96% probability of being more effective at lower costs. Compared with G_NT, TECCU saved €2250 (US $2463) per additional patient in remission (95% CI €-15,363 to 11,086; US $-16,817 to 12,135), and G_NT saved €538 (US $589) compared with G_control (95% CI €-6475 to 5303; US $-7088 to 5805). G_TECCU and G_NT showed an 84% and 67% probability, respectively, of producing a cost saving per additional quality-adjusted life-year (QALY) compared with G_control, considering those simulations that involved negative incremental QALYs as well. ConclusionsThere is a high probability that the TECCU Web platform is more cost-effective than standard and telephone care in the short term. Further research considering larger cohorts and longer time horizons is required. Trial RegistrationClinicalTrials.gov NCT02943538; https://clinicaltrials.gov/ct2/show/NCT02943538 (http://www. webcitation.org/746CRRtDN)